2015
DOI: 10.1007/s00268-015-3110-9
|View full text |Cite
|
Sign up to set email alerts
|

Surgical Resection for Hepatocellular Carcinoma with Concomitant Esophageal Varices

Abstract: These results suggest that HCC patients with EV and ICGR15 ≤17 % may be suitable for surgery, but patients with preoperative endoscopic blue color EV and red color sign need to be managed appropriately.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

4
9
0

Year Published

2016
2016
2021
2021

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 6 publications
(13 citation statements)
references
References 39 publications
4
9
0
Order By: Relevance
“…In this study, compared to the HCC patients without EGV, those patients with EGV had lower platelet counts; lower serum albumin levels; higher ALT, AST, and bilirubin levels; and higher Child-Pugh scores, indicating that they had poorer liver functional reserves, more active hepatic necro-inflammation, and even advanced fibrosis. These findings are consistent with the previous reports 18 20 21 29 . As these factors are critical in determining the prognosis of the patients with HCC, CSPH and EGV have been incorporated into the BCLC staging system and are widely applied as important references when selecting the treatment modalities in daily practice 24 30 .…”
Section: Discussionsupporting
confidence: 94%
See 3 more Smart Citations
“…In this study, compared to the HCC patients without EGV, those patients with EGV had lower platelet counts; lower serum albumin levels; higher ALT, AST, and bilirubin levels; and higher Child-Pugh scores, indicating that they had poorer liver functional reserves, more active hepatic necro-inflammation, and even advanced fibrosis. These findings are consistent with the previous reports 18 20 21 29 . As these factors are critical in determining the prognosis of the patients with HCC, CSPH and EGV have been incorporated into the BCLC staging system and are widely applied as important references when selecting the treatment modalities in daily practice 24 30 .…”
Section: Discussionsupporting
confidence: 94%
“…It is based on the negative impact of PHT and CSPH on the postoperative prognoses, including post-hepatectomy liver failure and long-term survival, demonstrated by several prospective studies and meta-analyses 9 29 32 33 . However, several recent studies demonstrate that CSPH is not a contraindication of resection for HCC 20 21 34 35 36 . Harada disclosed that HCC patients with EV could achieve similar long-term outcomes as those patients without EV if an indocyanine green retention test at 15 minutes (ICGR15) ≤17% 20 .…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Consistent with the BCLC staging system, previous reports demonstrated that patients with portal hypertension were not candidates for liver resection due to concomitant cirrhosis and thrombocytopenia, especially in Western countries (4,5). On the other hand, recent studies have reported that the presence of EV (6)(7)(8) or portal hypertension (9-12) is not an absolute contraindication for liver resection because the surgical outcomes of patients with HCC who underwent appropriate management for EV were acceptable. Thus, the outcomes of surgical resection for HCC in patients with portal hypertension are not completely understood.…”
Section: Introductionmentioning
confidence: 73%